Miejsce i rola kontroli budżetowej w systemie kontroli organizacji - Fjałkowska, Danuta (The Position and Role of Budget Control in the Organization Control System, 2005)
In the paper there have been presented selected questions concerning situating budget control in the organization management control system and the role that it plays in the control within the controlling system. There has been presented a model of relations between all kinds of control within the whole control system, particularly regarding the perspective and substance of control activities of budget control and of the control in controlling. There has been proven that the adequate importance conferred to the control function of budgeting and then the skilful exploitation of information from post-control deviations analyses not only have fundamental influence on the accomplishment of tasks of the controlling and management control systems, but also they ultimately define the quality of managerial decisions.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 156-164